2018
DOI: 10.32854/agrop.v11i10.1240
|View full text |Cite
|
Sign up to set email alerts
|

BÚFALO DE AGUA (Bubalus bubalis): UN ACERCAMIENTO AL MANEJO SUSTENTABLE EN EL SUR DE VERACRUZ, MÉXICO

Abstract: Objetivo: Analizar los principales indicadores asociados al manejo cultural del sistema búfalo en el sur de Veracruz, México (municipios de Acayucan, Sayula, Minatitlán, Soconusco, Hidalgotitlán, San JuanEvangelista, Las Choapas, Oluta, Jesús Carranza y Valle de Uxpanapan), para el desarrollo sustentable.Diseño/metodología/aproximación: El método de análisis de la presente investigación fue de tipo cuantitativo y el instrumento fue el cuestionario, los resultados se procesaron en el software estadísticoDYANE v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Lactation in female buffaloes in the study area begins shortly after birth and lasts an average of 240 days, but it is largely influenced by several factors such as breed, genetic background, season and period of calving, health status, and environmental factors [ 2 ]. This coincides with the values published by Hernández et al [ 77 ], Vázquez-Luna et al [ 78 ], and Gutiérrez et al [ 79 ] that found 240–270 days periods. The Italian Mediterranean breed, registered in the Buffalo Genealogical Book, has an average lactation period of 270 days [ 2 ].…”
Section: Milking Handlingsupporting
confidence: 92%
See 1 more Smart Citation
“…Lactation in female buffaloes in the study area begins shortly after birth and lasts an average of 240 days, but it is largely influenced by several factors such as breed, genetic background, season and period of calving, health status, and environmental factors [ 2 ]. This coincides with the values published by Hernández et al [ 77 ], Vázquez-Luna et al [ 78 ], and Gutiérrez et al [ 79 ] that found 240–270 days periods. The Italian Mediterranean breed, registered in the Buffalo Genealogical Book, has an average lactation period of 270 days [ 2 ].…”
Section: Milking Handlingsupporting
confidence: 92%
“…Obviously, the production costs of milk, meat, and derived dairy products such as cheese, among others, are fundamental in determining the levels of profitability of production units. In this regard, production in pasture systems is essential because of its advantages for reducing production costs [ 78 ].…”
Section: Handling Processing and Commercialization Of Milkmentioning
confidence: 99%
“…Commonly, reports indicate that milking time can be increased by 3 to 7 min when the stimulation is not appropriate by the handlers [ 36 ]. With respect to the lactation curve, the reported values range from 240–270 days [ 41 , 42 , 43 , 44 ], with a daily production of ~4–5 kg for Mediterranean buffaloes (data vary with different types of production, milking capacities, and milking methods) [ 2 , 3 , 45 ], and a total production of 1300–4500 L per lactation [ 46 ].…”
Section: The Mammary Gland: Pros and Contras Advantages And Disadvant...mentioning
confidence: 99%
“…La población de búfalos en México es mestiza principalmente de la raza Bufalipso, en particular los de la zona sur del estado de Veracruz, donde se pueden encontrar ejemplares con características de la raza Murrah, Mediterránea, Jafarabadi, Nili-Ravi, y algunos casos de Carabao (Hernández-Herrera et al, 2018). Históricamente, esta región de Veracruz se ha caracterizado por su vocación ganadera, sin embargo, la compleja realidad del campo mexicano ha llevado a un grupo de productores a optar por los búfalos en pastoreo como una alternativa interesante, debido al excelente comportamiento, eficiencia y productividad de los animales en sistemas de bajos insumos (Fundora et al, 2004;Hernández-Herrera et al, 2018). En México, la alimentación de los búfalos depende principalmente del pastoreo, salvo algunos suministros de sales minerales y rara vez la suplementación con silo (Hernández-Herrera et al, 2018).…”
Section: Introductionunclassified